Discounting the long-distant future: a simple explanation for the Weitzman-Gollier-puzzle - Wolfgang Buchholz; Jan Schumacher (Center for Economic Studies and ifo Institute (CESifo), 2008)
In this paper, we reconsider the debate on Weitzman's (1998) suggestion to discount the long-run future at the lowest possible rate, referring to Gollier (2004) and Hepburn & Groom (2007). We show that, while Weitzman's use of the present value approach may indeed seem questionable, its outcome, i.e. a discount rate that is declining over time, is nevertheless reasonable, since it can be justified by assuming a plausible degree of risk aversion.
Keywords: D40; E43; Q51; 330; Discount rates; uncertainty; risk aversion; Abzinsung; Intertemporale Allokation; Entscheidung bei Unsicherheit; Risikoaversion; Theorie